A research toolbox for regional data collection to support the conservation of large batoids: A case study on the critically endangered flapper skate (Dipturus intermedius) - Sophie L. Loca; Amy Garbett; Jonathan D. R. Houghton; James Thorburn; Oliver Ó Cadhla; Maurice Clarke; Gary Hannon; Liz Pothanikat; Paul A. Mayo; Ruairí Gallagher; Mark D. J. Hoppner; Patrick Colman Collins (Conservation Science and Practice)
Abstract Elasmobranchs, specifically skate species (superorder Batoidea), are at risk of extinction, with over one‐third currently listed as Endangered, exacerbated due to their k‐selected life strategy. A regional conservation approach is required to support the collection of rigorous, species‐specific data alongside collaborative efforts across sectors and jurisdictions. Skate species that extend beyond jurisdictional boundaries encounter additional complexities from divergent national legal frameworks, monitoring requirements, and conservation priorities, resulting in inconsistent data collection. Here we present an innovative research “toolbox,” initially devised for the Critically Endangered flapper skate (Dipturus intermedius) in the North‐East Atlantic, but applicable to most demersal elasmobranchs. This toolbox offers a systematic approach (Why, What, Who, Where, and When?) to obtain critical information for the conservation of elasmobranchs, with a focus on standardization and cross‐border collaboration. Recent advancements in understanding flapper skate ecology highlight the potential for regional conservation initiatives, emphasizing the importance of coordinated actions, and serve as an illustrative example within the context of the “toolbox.”